Modeling and Simulation of Lipid Membranes (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Cell membranes are complex structures able to contain the main elements of the cell and to protect them from the external surroundings, becoming the most fundamental interface in Biology. The main subject of this book is the study of the structure and characteristics of lipid membranes in a wide variety of environments, ranging from simple phospholipid membranes to complex systems including proteins, peptides, or oncogenes as well as the analysis of the interactions of the membrane components with small molecules and drugs. The scope of this book is to provide recent developments on membrane structure, composition and function by means of theoretical and experimental techniques, some of them combining computer simulations with available data obtained at the laboratory.This Special Issue aims to report brand new key contributions to the field and also to give an overview about the connection between experiments and computer simulations, addressing fundamental aspects and applied research in biological membranes, with particular attention paid to the applications of computer modeling and simulation to medicine.